Bioavailability and Pharmacokinetics Studies of Gamma Oryzanol - Hasan Hailat, Wafaa Mustafa (2004)
Rice bran oil was extracted from rice bran collected after four milling breaks that were used to process rice in Bernas factory, Sekinchan, Malaysia. Two organic solvents were used, a non-polar solvent that was hexane and a mixture of non-polar and polar, which were chloroform-methanol. Gamma oryzanol content of rice bran oil was then quantified, and the total antioxidant activity (TAA) was determined using FTC and TBA methods. After oil extraction, dietary fiber content was quantified in the four phases of defatted rice bran. Results showed that rice bran contained around 20 % lipid in the extracts of the two solvents used. Unlike oil yield, y-oryzanol content was affected by rice milling and the type of solvent used for extraction. For chloroform-methanol extract, phase 2 of rice milling contained the highest amount of y-oryzanol (5280 * 120 pprn), followed by phase 3 (3820 * 60 pprn), phase 4 (3400 * 100 pprn), and phase 1 (3000 * 80 pprn). The four phases of hexane extracts contained lower amount of yoryzanol than chloroform-methanol extracts. Phase 2 of rice milling contained the highest y-oryzanol content (4560 100 pprn), followed by phase 3 (2400 * 40 pprn),. phase 4 (2080 * 40 pprn), and phase 1 (1600 * 60 pprn). TAA studies showed that rice bran oil extracted from phase 2 of rice milling had significantly higher antioxidant activity than phase 1 (pc0.05). However, no significant differences were found among other phases (p0.05). It was found that rice bran is a good source of dietary fiber. However, fiber distribution was affected also by milling systems. Phase 2 of rice milling contained the highest amount of TDF which was 5 1.2 * 0.9 %, followed by phases 3, 1 and 4 that contained 45.2 * 1.0 %, 37.6 * 0.1 % and 35.5 * 0.8 % respectively. Caco-2 cell line was used as in vitro model to study y-oryzanol bioavailability from different formulations that were triolein solution, emulsion, tocotrienol rich fraction (TRF)-y-oryzanol emulsion, and microspheres. By day 9, cell line showed polarized monolayer properties as was detected from transepithelial electrical resistance (TEER) value (247.2 * 25.0 &m2) and phenol red diffusion (4.2 + 0.1 %). However, all experiments were conducted at day 18, to ensure that cells were fully polarized. In vitro digestion of 100 mg dose from each formulation resulted in low micellarization concentrations of y-oryzanol from both triolein solution and microspheres, that were 2 1 * 2 pglml digestate, and 20 * 2 pgml respectively. Nevertheless, micellarization concentrations were greatly improved to 5087 * 147 pglml and 5 160 + 228 pglml, from emulsion and TRF- y-oryzanol emulsion, respectively. After 10 h of incubation, only 0.43 * 0.02 pg (2.03 +_ 0.09 %) y-oryzanol was transported to the lower compartments from triolein solution. Cellular uptake of y-oryzanol from microspheres after the same period of incubation, increased to 1.25 * 0.09 pg (6.33 f 0.44 %). Gamma oryzanol absorption increased further to 1 14.94 * 2.02 pg (2.3 1 f 0.04 %) and 1 15.82 * 4.52 pg (2.24 + 0.05 %) from emulsion and TRF- y-oryzanol emulsion, respectively. Phannacokinetics of y-oryzanol was studied using rabbits. Gamma oryzanol emulsion was given as a single intravenous dose. Plasma level of y-oryzanol was quantified using HPLC. Plasma clearance of y-oryzanol followed two compartments model, indicating that y-oryzanol was distributed to the internal tissues. Elimination constant was 0.086 * 0.004 pg/ml.h, and the half-life was 8.040 * 0.360 h. Rabbits were used as in vivo model to study the bioavailability of y-oryzanol from triolein solution, microspheres, emulsion and TRF- y-oryzanol emulsion. The maximum concentration of y-oryzanol from triolein solution was 6.37 * 1.48 pg/ml, and improved to 130.30 * 30.40 pglml upon loading y-oryzanol in microspheres. However, in both formulations, the maximum concentrations were achieved after 2 h of ingestion. Where as the maximum concentrations of y-oryzanol from emulsion and TRF- y-oryzanol emulsion were 555 * 100 pglml and 525 * 95 pglml respectively and the t max. was 2 h. The absolute bioavailability of y-oryzanol emulsion was 6.61 * 0.86 %. The oral emulsion was used as a standard, so that the relative bioavailabilitiy (F relative) values of the other formulations were calculated. While F( relative) for y-oryzanol from triolein solution was only 0.51 * 0.06 %, it was significantly ('<0.05) increased to 16.63 * 1.71 % upon loading y-oryzanol in microspheres. Addition of TRF to y-oryzanol emulsion resulted in an increase of F (relative) to 109.60 * 13.83 %. However, this increase could be due to the preservative effect of TRF antioxidants. In conclusion, the bioavailability of y-oryzanol was low. However, its absorption increased around 200 times after emulsification and 33 times upon loading in microspheres.